Analisis Perilaku Konsumen, Perilaku Produsen, dan Pasar dalam Islam Pada Masyarakat - Riza Azzah Syafawati (Universitas Muhammadiyah Prof Dr Hamka, 2020)
In the current development of many economic activities that use the sharia system because the sharia system is not only beneficial to one party, but can benefit all parties, and the goal of the sharia system itself is to achieve mutual benefit. In the economy itself needs to pay attention about the behavior of consumers, producers and markets. Consumer behavior is a decision-making activity in purchasing activities. Consumer behavior can affect the number of requests and needs. Producer behavior is the activity of producing goods or services that can be used to meet consumer needs. This behavior influences the amount of production and supply of goods or services. Market behavior is a habitual pattern of the market including the decision making process as well as individual or organizational physical activities on certain products. The type of market also influences the prices of goods and services. In Islam, these three behaviors must be based on Islamic teachings, namely, monotheism, justice, nubuwah, caliph, ma'ad. It aims to bring benefits and benefit to the community and achieve the blessings and blessings of Allah SWT. Key Word: Consumer Behavior, Producer Behavior, Market